Sustainable and Affordable Mobility for All - Putting the Heart Back into Technology - Borroni-Bird Christopher (SAE International, 2025)
This offers a bold, yet practical vision for the future of transportation. Drawing from deep technical expertise and global experience, Chris Borroni-Bird presents a transformative approach to the automotive industry, tackling critical issues like economic development, environmental sustainability, and universal access. This groundbreaking book explores how advanced technologies such as electric, autonomous, and connected vehicles can revolutionize not only personal mobility but also urban transport and public systems. It calls for a shift toward ""right-sized"" vehicles, designed to meet real-world needs without over-engineering.Borroni-Bird's solutions are scalable and adaptable to both developed and developing markets, ensuring affordable and sustainable mobility for all. With insights from ten years of rapid innovation, including ridesharing platforms and robotaxis, this book blends technology, human factors, and sustainability to inspire a future where transportation is efficient, accessible, and environmentally responsible. A must-read for industry leaders, strategists, and innovators, the advocates for a world where we put the heart back into technology - making mobility solutions that work for people, planet, and profit. Join the movement for a smarter, more sustainable future in transportation.